Factors that Contribute to Nursing and Medical Students‟ Perceptions of the Nurse-Physician Relationship (International Journal of Studies in Nursing, 2019)
Background: Biases and preconceptions regarding future working relationships have the potential to impact professional interactions. Purpose: The purpose of this qualitative study was to investigate the factors that contribute to nursing and medical students‟ perceptions of the nurse-physician relationship. Method: This was a qualitative, phenomenological, explorative study with a descriptive design. Eight nursing students and eight medical students were interviewed for this study and themes were carefully extracted from their responses. A series of open-ended questions were asked that were intended to elicit honest, thoughtful responses regarding how they view the other profession, their relationship, and thoughts on the quality of future professional collaboration. Social identity theory was used as the conceptual framework to guide this study. Themes were then extracted from the interviews. Results: The main themes found were in the areas of attitudes and behaviors. Nursing students had more positive than negative comments about interdisciplinary attitudes, but they had slightly more negative comments regarding interdisciplinary behaviors. Medical students commented far more on interdisciplinary behaviors than on attitudes, with both categories turning out more positive than negative. Specific subthemes included medical students‟ concern with sexism against female physicians and their high degree of concern over how interdisciplinary relationships affect the patient. Nursing students believed the relationship would be respectful depending on the unit. However, most of them expressed concern with how negative behaviors impact the patient. Conclusion: Learning standout themes from nursing and medical students‟ perceptions of their future working relationships can aid in finding barriers that can be addressed. Future research would be beneficial to discover themes on a larger scale.